April 15th war and hemodialysis patients in Sudan: a cross-sectional study - Malaz Hassan Dafaalla Idrees; Moez Mohammed Ibrahim Bashir; Balqees Abdeen Ahmed Mohamed; Amal Essam Ali Ahmed; Hamid Mohieldin Mohamed Abdalla; Kamil Mirghani Ali Shaaban (BMC Public Health)
Abstract Background On April 15th, 2023, intense clashes involving heavy weapons and airstrikes occurred between the Sudanese Armed Forces (SAF) and the paramilitary Rapid Support Forces (RSF) in Khartoum, the capital of Sudan, leading to the displacement of almost 8.1 million people. The ongoing armed conflict in Sudan has led to a worsening humanitarian catastrophe, posing serious challenges to the country’s health-care system and even its collapse. Healthcare facilities have been severely affected, with barely one-third of hospitals operating in conflict zones. Hemodialysis patients are among the most affected by this war’s aftermath, which ranges from obvious dangers like violence-related injuries and deaths to more indirect effects like the suspension of access to preventive and curative medical care. Methods This was a descriptive cross-sectional multicenter health facility-based study aiming to study the impact of the April 15 war on hemodialysis patients in Sudan. The study was conducted in five centers in four different states in Sudan, including Gezira State, Red Sea State, River Nile State, and Kassala State. The study included 316 participants. Data was collected using structured interviews guided by a questionnaire. The questionnaire encompassed five primary domains: demographic data, healthcare access (Levesque’s Conceptual Framework of Access), physical implications, psychological impact (Generalized Anxiety Disorder scale and Patient health questionnaire), and quality of life (Kidney disease quality of life 36 scales). Statistical Package for the Social Sciences (SPSS) version 26 was used for data analysis. Results This study involved 316 participants, with an average age of 47.14 and 63.9% being males. After the war, 74.7% reported being unemployed. 30.1% of participants had to flee their homes, and 18.7% had a renal ailment limiting their travel. Among the components of healthcare access affordability, it received the lowest score (5.6 out of 10). More than half of the participants were unable to maintain their regular hemodialysis sessions (56.9%) throughout the war, and 65.2% of the participants developed medical complications as a result. The GAD assessment showed 62.7% of participants had significant anxiety symptoms, while 40.5% had significant depression symptoms. Conclusion Hemodialysis patients’ suffering has increased as a result of the war. Hemodialysis patients experience severe mental health problems in addition to physiological problems, including depression and anxiety, as a result of internal displacement and their inability to continue regular hemodialysis sessions. The study advocates for the implementation of a permanent ceasefire in conflict zones to ensure the delivery of critical humanitarian medical aid, particularly hemodialysis care. The study encourages stronger advocacy for hemodialysis in war-torn areas as well as collaboration with international organizations to provide such specialized care. Finally, it encourages the use of telemedicine services as a backup plan to provide continuous hemodialysis consultation and care in the event of conflict disruptions.